Exercise‐induced thoracic outlet syndrome and concomitant osteomyelitis in cervical rib with a possible familial origin: A case report - Ammara Bint I Bilal; Mohammadshah Isam Gul; Fateen Ata; Renan E. Ibrahem; Muhammad I. Danjuma (Clinical Case Reports, 2022)
Abstract Cervical ribs are rare and usually asymptomatic. Occasionally, they can cause nerve impingements and compressive symptoms. In cervical ribs, osteomyelitis secondary to trauma is unheard of. We report such a case made more interesting by the familial presence of bilateral cervical ribs in two generations, indicating a familial origin.